Academic Performance Assessment Prediction Model Using the Adaptive Neuro-Fuzzy Inference System Method - Mardi Turnip; M. Arif Almahdi; Timi Tampubolon; Ade Irma Suryani; Astri Milleniar Marbun; Cindy Cynthia; Ester Ayu S. Marpaung (Yayasan Kita Menulis, 2023)
Performance evaluation of Human Resources is an important part of an organization or company. One of the HR in tertiary institutions that must be evaluated is academic performance. The author conducted research on the factors of academic performance assessment. Therefore, we need a system that can classify academic performance optimally in order to improve the quality of academic performance. In this research, we construct a predictive model for academic ability evaluation using Adaptive Neuro-Fuzzy Inference System method. The ANFIS method shows a very good data accuracy of 92.20%. From each variable motivation to work appraisal show is a Good, competence to work appraisal = Good, compensation to work appraisal show is a Good, responsibility to work appraisal show is a Good, and job satisfaction to work assessment show is Good.